Use of Retrograde Cardioplegia in Coronary Artery Bypass Graft Surgery - Dawood, Adil K. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Retrograde Cardioplegia is a widespread method for myocardial protection in coronary bypass surgery and to abroad range of open heart surgical procedures in addition to antigrade Cardioplegia, Objectives: Is to evaluate the use of retrograde cardioplegia and its advantages in coronary bypass surgery at Ibn Al-Nafees Teaching Hospital, Department of Cardiac Surgery, Patients and methods: This is a retrospective study that was conducted at Ibn Al-Nafees Teaching Hospital from the first of January to the first of October 2015, fifty patients with coronary artery dieses were admitted to the hospital and coronary artery bypass graft (CABG) surgery was done under cardiopulmonary bypass using retrograde cardioplegic canula through the coronary sinus from the right atrium in addition to antigrade cardioplegia from aortic root for myocardial protection during surgery on arrested heart using cold crystalloid cardioplegia. Results: The fifty patients who were studied were operated upon, the age of patients was ranged from 37-79 year with a mean age 0f 60 year and male to female ratio was 3:1. 25 patients (50%)had left main coronary artery lesion ,all underwent bypass surgery on cardiopulmonary bypass machine using retrograde cardioplegia in addition to antegrade. in 45 patient (90%) the heart picked up (beating) spontaneously without using D.C shock while in five patient (10%) internal D.C shock was required for beating the heart from the state of ventricular fibrillation .In all patients , coming off from heart lung machine was easy with a small dose of inotropics agents. Intra aortic balloon pump was used in one patient. Only one early death observed in this study due to post operative renal failure. Conclusion: Retrograde cardioplegia is a safe , widespread, and effective method for myocardial protection in addition to antegrade cardioplegia and this achieved longer time of protection during cardiac arrest . This method is very useful in patients with left main coronary artery disease.